Practice makes imperfect: Positive correlation between practice and implicit distraction in asymptomatic individuals with Alzheimer's disease pathology. (20th December 2022) - Hung, Shao‐Min (Sean); Wu, Daw‐An; Shimojo, Shinsuke; Arakaki, Xianghong
Abstract: Background: Our recent research showed that cognitively healthy older participants with higher biochemical risk to develop Alzheimer's disease were more distracted by an incompatible and implicit visual stimulus, which was not observed in low‐risk older participants. This finding shed light on using psychophysical experiments to early identify high‐risk older participants. Here we further examined the role of practice based on our findings in the young healthy participants where implicit distracting information processing was enhanced after practice. We expected the effect of practice on processing the implicit distractor in high‐risk and low‐risk participants would bifurcate. Methods: Cognitively healthy (CH) participants were recruited from the local community, consisting of two subgroups based on cerebrospinal fluid (CSF) proteins: with normal beta amyloid42 /total tau ratio (CH‐NAT, low‐risk, n = 17) or pathological beta amyloid42 /total tau ratio (CH‐PAT, high‐risk, n = 19). Their age, gender, education year, and days between the two sessions were all comparable. A task‐switching Stroop task was implemented. Each trial contained two stimuli, and participants had to name the color or word of a colored word for each stimulus with button press. Only correctly responded trials (correct responses to both stimuli in the trial) were analyzed. Below we reported the performance on the second stimulus (target). Results: In general, participants showed a significant practice effect over the two sessions. Their reaction times (RT) decreased by 6.19 % (3.04 %), and accuracy rates (ACC) increased by 6.09 % (1.04 %). These results showed evident improvement on performance. Critically, we further investigated the relationship between the practice effect and the subliminal distractor effect. We found a significant positive correlation in high‐risk participants between the practice effect and the strength of subliminal RT interference ( p = 0.03). That is, the more RT decrease observed in a high‐risk individual, the stronger interference was found. Such a linkage was not found in low‐risk participants ( p > 0.05). Conclusion: Our results clearly show that high‐risk and low‐risk asymptomatic older participants operate on different cognitive schemes to process implicit distracting sensory information. Intriguingly, better practice effect is correlated with stronger implicit distraction only in high‐risk participants.